Experimental and theoretical triple differential cross sections for electron-impact ionization of Ar (3p) for equal energy final state electrons. (5th September 2016) - Amami, Sadek; Ozer, Zehra N; Dogan, Mevlut; Yavuz, Murat; Varol, Onur; Madison, Don
Abstract: There have been several studies of electron-impact ionization of inert gases for asymmetric final state energy sharing and normally one electron has an energy significantly higher than the other. However, there have been relatively few studies examining equal energy final state electrons. Here we report experimental and theoretical triple differential cross sections for electron impact ionization of Ar (3p) for equal energy sharing of the outgoing electrons. Previous experimental results combined with some new measurements are compared with distorted wave born approximation (DWBA) results, DWBA results using the Ward–Macek (WM) approximation for the post collision interaction (PCI), and three-body distorted wave (3DW) which includes PCI without approximation. The results show that it is crucially important to include PCI in the calculation particularly for lower energies and that the WM approximation is valid only for high energies. The 3DW, on the other hand, is in reasonably good agreement with data down to fairly low energies.